The implications of the new regulations for the universities - Barbara Robertson (AOSIS, 1985)
The inclusion of nursing education into the tertiary education system of the country is indeed a milestone in the development of the nursing profession. Nursing education has now been recognised by the country and it is up to all of us to ensure that nurses educated through this new system are competent and can provide quality service to the health consumer.